KEBIASAAN MAKAN ANAK BALITA GIZI KURANG PADA KELUARGA NELAYAN DI DESA KWALA SERAPUH KECAMATAN TANJUNG PURA - Sri Dewi Haryati; Desi Ernita Amru; Anisya Selvia (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2022)
Reproductive health starts from conception, infants, toddlers to old age. Toddlers are an age group that is vulnerable to nutrition and disease prone. The purpose of this study was to analyze the eating habits of malnourished children under five in fishermen's families in Kwala Serapuh Village, Tanjung Pura District. Type of research is a qualitative research with a case study strategy. Data collection is done by observation and interviews. The informants of this study were mothers of children under five with malnutrition. The results showed that the eating habits of malnourished children under five in fishermen's families were not good because the frequency of eating 2 (two) times a day did not meet the quantity and quality of food for toddlers. The type of food does not vary because it is considered extravagant. It is hoped that midwives and public health officers will increase counseling about good eating habits in toddlers so that they can reduce the incidence of under-five nutritional status